Interaction Model of Langkap Plant (Arenga obtusifolia Blumme Ex. Mart) with The Javan Rhino (Rhinoceros sondaicus Desmarest, 1822) at Ujung Kulon Nasional Park : Cibandawoh and Cikeusik Resort - AYU NINDYANINGRUM (NIM : 11513015), ANNISA
The Javan Rhino (Rhinoceros sondaicus Desmarest, 1822) consumes about 50% of species and 70% of families of 453 species and 92 plant families found in Ujung Kulon. However, the presence of a native plant of Ujung Kulon National Park, langkap (Arenga obtusifolia), is considered to be capable of reducing the abundance of Javan rhino feed plant. The purpose of this research is to determine the interaction between feed plants of Javan Rhino with langkap by analizing langkap’s influence to abundance, diversity, and presence of feed plant species of Javan Rhino. Data was collected in Ujung Kulona National Park for nine days from May 23rd – June 7th 2017. This research is conducted at the three locations with different langkap stand conditions, categorized as criteria A (location of no langkap density), criteria B (location of stands with medium density), and criteria C (location of stands with high density). Data analysis used are Shannon-Wiener (H’) diversity index, Important Value Index, and species presence association (Chi-square analysis). Feed plant species tend to have the highest H’ value in criteria A, specifically in seedlings and herbs (H’ = 2.91), shrubs and stakes (H’ = 2.03), and pole (H’ = 0.97). While at the tree level, the highest H’ value is in criteria B (H’ = 2.13). This may indicate that langkap density interacts negatively with the diversity of plant species. Based on the important value index, it is found that langkap dominates the various levels of plant growth stages in criteria B and criteria C. The more dominant the langkap, causes the abundance of plant species to decrease. Abundance of feed plant species at different levels of tree and habitus life tend to interact negatively with langkap density. Analysis of the presence association of feed plant species and langkap showed that both tend not to associate from a sample of 98 pairs of feed plants with langkap. It can be concluded that langkap and feed plants interacted negatively at the research sites.